2015
DOI: 10.1007/s12274-015-0787-x
|View full text |Cite
|
Sign up to set email alerts
|

High-performance solar-blind ultraviolet photodetector based on electrospun TiO2-ZnTiO3 heterojunction nanowires

Abstract: High-performance solar-blind UV (ultraviolet) photodetectors (PDs) based on low-dimension semiconducting nanostructures with high sensitivity, excellent cycle stability, and the ability to operate in harsh environments are critical for solar observations, space communication, UV astronomy, and missile tracking. In this study, TiO 2 -ZnTiO 3 heterojunction nanowire-based PDs are successfully developed and used to detect solar-blind UV light. A photoconductive analysis indicates that the fabricated PDs are sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Hybrid nanostructures are considered as most promising sensitive photodetection materials because they offer not only high photoconductive gain and the property benefits of 1D nanostructures, but also the added benefit of multifunctional or new properties arising from the synergistic effects of combining heterojunction materials. Chong et al [ 116 ] successfully developed TiO 2 -ZnTiO 3 heterojunction nanowire-based photodetectors and used them to detect solar-blind UV light. As shown in Figure 14 , further analysis indicated that the rich existence of grain boundaries within the TiO 2 -ZnTiO 3 nanowire can greatly decrease the dark current and recombination of the electron-hole pairs, and thereby significantly increase the device’s photosensitivity, spectral responsivity (1.1 × 10 6 A/W), and external quantum efficiency (4.3 × 10 8 %).…”
Section: New Types Of Uv Dtectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid nanostructures are considered as most promising sensitive photodetection materials because they offer not only high photoconductive gain and the property benefits of 1D nanostructures, but also the added benefit of multifunctional or new properties arising from the synergistic effects of combining heterojunction materials. Chong et al [ 116 ] successfully developed TiO 2 -ZnTiO 3 heterojunction nanowire-based photodetectors and used them to detect solar-blind UV light. As shown in Figure 14 , further analysis indicated that the rich existence of grain boundaries within the TiO 2 -ZnTiO 3 nanowire can greatly decrease the dark current and recombination of the electron-hole pairs, and thereby significantly increase the device’s photosensitivity, spectral responsivity (1.1 × 10 6 A/W), and external quantum efficiency (4.3 × 10 8 %).…”
Section: New Types Of Uv Dtectorsmentioning
confidence: 99%
“… ( a ) Schematic of single TiO 2 -ZnTiO 3 nanowire-based photodetector; ( b ) I–V curves of a single nanowire-based photodetector; inset is a corresponding SEM image of the device; ( c ) Reproducible on/off switching illuminated by 320 nm light with intensity of 186.2 μW/cm 2 at a bias of 2 V; ( d ) Spectroscopic photoresponse of the photodetector under UV illumination under light with varying wavelengths (250 nm: 208.5 μW/cm 2 , 290 nm: 185.5 μW/cm 2 , 320 nm: 186.2 μW/cm 2 , 330 nm: 191.2 μW/cm 2 , 350 nm: 176.1 μW/cm 2 , 360 nm: 180.9 μW/cm 2 , 370 nm: 202 μW/cm 2 ) at a bias of 2 V. Ref. [ 116 ] Copyright 2015, Tsinhua University Press. …”
Section: Figurementioning
confidence: 99%
“…As shown in Figure b (the down‐right inset in Figure b is the typical SEM image of the PD), the I–V curves exhibit linear relationship with the increase of applied biases, suggesting that an ohmic contact has been built up between the CsPbI 3 nanotubes and Au electrodes, which could reduce the contact barriers, leading to the enhanced performance of the device . The dependence of the photocurrent on the light intensity is described by a power law: I = αP θ , where α is a constant for a given wavelength, P is the light intensity, and θ is the exponent, which determines the response of the photocurrent to light intensity. Thereby, the θ of 0.59 is obtained by fitting the curve in Figure c.…”
Section: Resultsmentioning
confidence: 94%
“…To demonstrate their stability in high‐temperature environment, the temperature‐dependent time responses of single B‐doped SiC nanobelt PD are measured under 405 nm light with a power density of 0.14 mW·cm −2 at a bias of 5.0 V, as shown in Figure a. They present that both dark current and photocurrent increase with the increase of the working temperatures, which could be mainly originated from the hot‐electron effect . In view of the raised temperatures, the increased thermally excited electrons could reduce the resistance of semiconductor, resulting in a larger dark current and photocurrent.…”
Section: Resultsmentioning
confidence: 99%